POSSIBILITIES OF APPLICATION OF JET HEATING OF METAL BEFORE ROLLING - V. I. Timoshpolski; I. A. Trusova; P. E. Ratnikov (Литьë и металлургия)
The possibilities of application of the metal jet heating before rolling are shown.